Survey of Hypertension Diabetes and Obesity in Three Nigerian Urban Slums - Zaidat Adesola Musa; Adeniyi Kazeem Adeneye; Adejuwon Adewale Adeneye; Pius Adejoh; Lekan John Oyefara; Olaoluwa Pheabian Akinwale; Kolawole Solomon Oyedeji; Medinat Ayobami Sulyman (Tehran University of Medical Sciences, 2013)
Background: Non-communicable diseases (NCDs) exist in slums as the inhabitants adopt an urbanized lifestyle which places them at a higher risk for. Lack of knowledge about the morbidity, complications and the method of control contributes to a large percentage of undetected and untreated cases.Methods: This cross-sectional survey polled 2,434 respondents from Ijora Oloye, Ajegunle and Makoko, three urban slums in Lagos metropolis, southwestern Nigeria between June 2010 and October 2012. We investigated the prevalence of hypertension, diabetes and obesity. Respondents signed consent forms and their health conditions were documented based on self-reported history of diabetes, hypertension and family history using a semi-structured questionnaire. Diagnostic tests; weight and height for body mass index, blood glucose, and blood pressure were performed.Results: More than one quarter of the participants were suffering from hypertension and only half of this were diagnosed earlier, while a further few were already on treatment. Therefore on screening, it had been possible to diagnose over three hundred more respondents, who were not previously aware of their health status. The respondents' BMI showed that more than half of them were either overweight or obese and are at risk for diabetes, while 3.3% were confirmed as being diabetic, with their sugar levels greater than the normal range.Conclusion: This study therefore revealed the near absence of screening programs for chronic diseases such as hypertension, diabetes and obesity in these urban slums. This was further confirmed by the detection of new and undiagnosed cases of hypertension in about one quarter of the respondents.